Legal Uncertainty in Dispute Resolution of Ijarah Muntahiya Bi al-Tamlik Contracts in Indonesia: A ḥifẓ al-māl Perspective - Moh. Nurul Huda; Bambang Tri Bawono; Gunarto Gunarto; M. Dias Saktiawan (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
Legal uncertainty in the construction of ijarah muntahiya bi al-tamlik (IMBT) contracts within the Compilation of Sharia Economic Law (KHES) arises in two areas. First, ambiguity occurs in the transfer of ownership at the end of the lease term, which may use either a sale or a hibah (grant) scheme. Second, dispute resolution is often implemented disproportionately, causing financial harm to the musta’jir. This study employs normative juridical research with a statutory approach, as inconsistencies are found between legislation and fundamental legal principles. The findings indicate that ownership transfer in IMBT contracts should only be carried out through a sale mechanism. Using hibah is inconsistent with its classification as a tabarru’ contract and contradicts Article 362 of KHES. Moreover, dispute resolution should not treat the musta’jir as indebted and force the sale of the leased object before the contract term ends. Instead, proportional penalties, explicitly stipulated in the contract, provide a fairer mechanism. These results highlight the urgency of reformulating IMBT contract practice in Indonesia. For Sharia financial institutions, implementing clearer ownership transfer rules and fair dispute resolution mechanisms will enhance legal certainty, protect the parties involved, and strengthen public trust in Sharia-compliant financial products.